Stable zinc anodes enabled by a zincophilic polyanionic hydrogel layer - Yang, Jin-Lin (2022)
The practical application of the Zn-metal anode for aqueous batteries is greatly restricted by catastrophic dendrite growth, intricate hydrogen evolution, and parasitic surface passivation. Herein, a polyanionic hydrogel film is introduced as a protective layer on the Zn anode with the assistance of a silane coupling agent (denoted as Zn-SHn). The hydrogel framework with zincophilic -SO3 - functional groups uniformizes the zinc ions flux and transport. Furthermore, such a hydrogel layer chemically bonded on the Zn surface possesses an anti-catalysis effect, which effectively suppresses both the hydrogen evolution reaction and formation of Zn dendrites. As a result, stable and reversible Zn stripping/plating at various currents and capacities is achieved. A full cell by pairing the Zn-SHn anode with a NaV3 O8 ·1.5 H2 O cathode shows a capacity of around 176 mAh g-1 with a retention around 67% over 4000 cycles at 10 A g-1 . This polyanionic hydrogel film protection strategy paves a new way for future Zn-anode design and safe aqueous batteries construction.